- #1

- 1

- 0

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- #1

- 1

- 0

- #2

Gold Member

MHB

- 13,298

- 11

\(\displaystyle \frac{\sin(\theta)}{2x}=\frac{\sin(2\theta)}{3x}\)

Can you show this implies:

\(\displaystyle \cos(\theta)=\frac{3}{4}\)?

- #3

Gold Member

MHB

- 13,298

- 11

To follow up:

We have:

\(\displaystyle \frac{\sin(\theta)}{2x}=\frac{\sin(2\theta)}{3x}\)

Multiplying through by \(6x\) and using a double-angle identity we obtain:

\(\displaystyle 3\sin(\theta)=4\sin(\theta)\cos(\theta)\)

As presumably \(\sin(\theta)\ne0\) (otherwise our triangle is degenerate) we may divide by this quantity to get:

\(\displaystyle 3=4\cos(\theta)\implies \cos(\theta)=\frac{3}{4}\)

And so the 3 interior angles are:

\(\displaystyle \theta=\arccos\left(\frac{3}{4}\right)\)

\(\displaystyle 2\theta=2\arccos\left(\frac{3}{4}\right)\)

\(\displaystyle \pi-3\arccos\left(\frac{3}{4}\right)\)

As these 3 angles are different, we know we have a scalene triangle, and knowing this will help.

Now, let's use the Law of Cosines as follows:

\(\displaystyle (2x)^2=(3x)^2+15^2-2(3x)(15)\cos(\theta)\)

\(\displaystyle 4x^2=9x^2+15^2-90x\left(\frac{3}{4}\right)\)

Arrange resulting quadratic in standard form:

\(\displaystyle 2x^2-27x+90=0\)

Factor:

\(\displaystyle (2x-15)(x-6)=0\)

Because \(2x\) cannot be 15 as all three sides must have different lengths, we reject that root and are left with:

\(\displaystyle x=6\)

And so, our triangle has:

Side \(a\) is 12 cm and the angle opposing it is about \(\displaystyle 41.4^{\circ}\).

Side \(b\) is 18 cm and the angle opposing it is about \(\displaystyle 82.8^{\circ}\).

Side \(c\) is 15 cm and the angle opposing it is about \(55.8^{\circ}\).

View attachment 9699

We have:

\(\displaystyle \frac{\sin(\theta)}{2x}=\frac{\sin(2\theta)}{3x}\)

Multiplying through by \(6x\) and using a double-angle identity we obtain:

\(\displaystyle 3\sin(\theta)=4\sin(\theta)\cos(\theta)\)

As presumably \(\sin(\theta)\ne0\) (otherwise our triangle is degenerate) we may divide by this quantity to get:

\(\displaystyle 3=4\cos(\theta)\implies \cos(\theta)=\frac{3}{4}\)

And so the 3 interior angles are:

\(\displaystyle \theta=\arccos\left(\frac{3}{4}\right)\)

\(\displaystyle 2\theta=2\arccos\left(\frac{3}{4}\right)\)

\(\displaystyle \pi-3\arccos\left(\frac{3}{4}\right)\)

As these 3 angles are different, we know we have a scalene triangle, and knowing this will help.

Now, let's use the Law of Cosines as follows:

\(\displaystyle (2x)^2=(3x)^2+15^2-2(3x)(15)\cos(\theta)\)

\(\displaystyle 4x^2=9x^2+15^2-90x\left(\frac{3}{4}\right)\)

Arrange resulting quadratic in standard form:

\(\displaystyle 2x^2-27x+90=0\)

Factor:

\(\displaystyle (2x-15)(x-6)=0\)

Because \(2x\) cannot be 15 as all three sides must have different lengths, we reject that root and are left with:

\(\displaystyle x=6\)

And so, our triangle has:

Side \(a\) is 12 cm and the angle opposing it is about \(\displaystyle 41.4^{\circ}\).

Side \(b\) is 18 cm and the angle opposing it is about \(\displaystyle 82.8^{\circ}\).

Side \(c\) is 15 cm and the angle opposing it is about \(55.8^{\circ}\).

View attachment 9699

Share:

- Replies
- 2

- Views
- 560

- Replies
- 8

- Views
- 440

- Replies
- 4

- Views
- 477

- Replies
- 6

- Views
- 851

- Replies
- 2

- Views
- 394

- Replies
- 1

- Views
- 416

- Replies
- 1

- Views
- 497

- Replies
- 19

- Views
- 833

- Replies
- 3

- Views
- 435

- Replies
- 1

- Views
- 516